1985
DOI: 10.2337/diacare.8.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of a Marked “Dawn Phenomenon” in Diabetic Subjects Treated by Continuous Subcutaneous Insulin Infusion

Abstract: We assessed the quality of overnight glycemic control and the frequency of the "dawn phenomenon" (nadir-0800 h glycemic increase) in 41 insulin-dependent diabetic patients treated by continuous subcutaneous insulin infusion (CSII). Mean plasma glucose levels were near-normal during the 24 h and, in particular, constant throughout the night. In a subset of six patients overnight plasma free insulin concentrations were also constant during CSII. The majority of profiles (88%) showed a glucose nadir from 2.0 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 6 publications
(9 reference statements)
3
26
0
Order By: Relevance
“…This is similar to our recent study ofthe effect of infused catecholamine on glucose metabolism (28). In this context, it is important to point out that the insulin levels used in the present study during the clamps are clinically relevant as corresponding levels are frequently seen in patients with type I diabetes during both conventional insulin therapy and continuous subcutaneous insulin infusion (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to our recent study ofthe effect of infused catecholamine on glucose metabolism (28). In this context, it is important to point out that the insulin levels used in the present study during the clamps are clinically relevant as corresponding levels are frequently seen in patients with type I diabetes during both conventional insulin therapy and continuous subcutaneous insulin infusion (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Morning hyperglycemia can be overcome by increasing insulin doses, but only at the expense of lower nighttime glucose levels (65). Bolli et al (34) demonstrated that posthypoglycemic hyperglycemia is the result of both dissipation of injected insulin and activation of counterregulatory systems, principally adrenomedullary epinephrine secretion (20), perhaps coupled with GH secretion, in patients with IDDM.…”
Section: In Addition To Dissipation Of Insulin and Nocturnal Gh Secrementioning
confidence: 98%
“…It should be emphasized that the nighttime to morning increase in plasma glucose is variable in a given patient (64) and absent or rather minor in many patients (65,66) with IDDM. Morning hyperglycemia can be overcome by increasing insulin doses, but only at the expense of lower nighttime glucose levels (65).…”
Section: In Addition To Dissipation Of Insulin and Nocturnal Gh Secrementioning
confidence: 99%
“…In the first set ofexperiments (study I), to induce moderate hypoglycemia, insulin (Actrapid HM U-40; Novo Research Institute, Copenhagen, Denmark), diluted to 1 U/ml in 100 ml of0.9% NaCl containing 2 ml of the subject's blood, was intravenously infused at the rate of 0.30 mU* kg-' * min' from 0 to 180 min and 0.40 mU -kg-' -min' from 180 to 480 min with a syringe pump (Harvard Apparatus Co., Inc., The Ealing Corp., South Natick, MA). This intravenous rate ofinsulin infusion was chosen to reproduce the mild hyperinsulinemia observed in previous studies during subcutaneous insulin infusion in normal man (1)(2)(3)(4)(5)(6), and to simulate the type of hypoglycemia that may develop in diabetic patients undergoing intensive insulin therapy (8,9,(22)(23)(24)(25).…”
Section: Methodsmentioning
confidence: 99%